SISTEM INFORMASI PENDATAAN MURID BULUTANGKIS DI GELANGGANG OLAH RAGA PALM RAYA - Paris Pratama; Wirda Fitriani; Zulfahmi Syahputra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Badminton is a sport that is often done in a closed room. Palm Raya is one of the badminton training venues that is open to the public. Students can take part in the types of training offered here. The information system was built to collect data on students who have joined in Palm Raya. This information system serves to make it easier for related parties to search student data if needed someday so as to make it easier to search data. This information system is only used by the admin of Palm Raya. With this information system, the ease of managing student data at Palm Raya will be better than before, which only uses conventional methods.Keywords: badminton, student, information system, palm raya.